Value orientation as resistance to utility of STEM-driven innovations to promote environmental conservation among public - Syed Abdullah, Sharifah Intan Sharina; Zainudin, Zaida Nor; Mohd Shahali, Edy Hafizan; Abd Rahman, Norshariani; Abdul Rahim, Fitriya (Human Resource Management Academic Research Society, 2019)
Innovations is one of STEM products that will significantly impact people’s life. However, the ability of STEM-driven innovation to solve a particular problem may be different from one place to another. It depends on the values preserved by a particular society. This study investigate how value orientation may be the resistance to utility of reverse vending machine (RVM). The current study adopted qualitative research approach. Qualitative data were collected from Malaysian public through comments they left on an article posted on a Facebook group page about RVM. The 281 comments were analyzed thematically. Three themes presented in this article are: i) egoistic oriented response; ii) biospheric oriented response; and iii) anticipation of the adverse effects of reverse vending machine. This study suggests there is a need for education reorientation, especially STEM education in Malaysia. STEM education should develop thinking citizens that are able to think and make their own decisions based on sound judgment in determining what counts as proper behavior.